Advancement in Glucose Biosensors and Current Development of Electrochemical Sensing - Pramanik, Rajib; Ikbal, Mohammed; Mishra, Nimai; Parvin, Shabnam; Hoque, Rabiul (Current Physical Chemistry, 2025)
Since the introduction of the first enzyme electrode in 1962, the area of glucose biosensing has undergone substantial expansion and advancement. The ongoing development of sensing platforms has been achieved by extensive study on different immobilization methods and improvements in electron transfer efficiency between enzymes and electrodes. The advancement of nanostructures and their composites has further accelerated this process. Some noteworthy examples include carbon nanotubes, graphene/graphene oxide, and metal oxides. Nanomaterials are used in biosensors to optimize the immobilization process and enhance the electrocatalytic activity of glucose. This article provides a concise overview of the development of glucose biosensors, emphasizing several iterations and recent patterns in utilizing nanostructures for glucose detection, with or without using enzymes. A complete overview was created by collecting, evaluating, analyzing, and reviewing the most recent literature on electrochemical glucose biosensors, including enzymatic and non-enzymatic approaches. The paper comprehensively analyzes the evolution from the 1st to the 4th generation, focusing on the prospects for the most recent generation of glucose biosensors. In addition, this article examines the many mechanisms of glucose sensors using complex materials and methods for glucose detection technology. We specifically aim to comprehend the mechanisms revealed by different electrochemical techniques that enhance glucose oxidation and its interaction with the electrode. To heighten our comprehension of glucose oxidation, we examine the historical background of these biosensors, progress made in improving electron transfer, the creation of several sensing platforms that utilize nanomaterials, and their resulting performance.
Keywords: diabetes